Urban and Peri-urban Dairy Production System in Semi-arid Region of Uttar Pradesh (Indian Journal of Animal Production and Management, 2024)
Urban and peri-urban area are dairy intensive area which provides milk and milk products to the  urban areas and thus help to generates regular income to these farmers. With rise in the urbanization  the demands of milk and milk products is rising and farmers should be prepared the accelerating  demands. The production of dairy animal is mostly influenced by feeding, management, health care  and management practices with a clear understanding about scientific knowledge. Therefore, the  efforts are made to assess the knowledge level of farmers and the factors affecting the dairy  production in urban and peri-urban areas. This study was conducted purposively to assessing the  Urban and Peri-urban Dairy production system in semi-arid region of Uttar Pradesh. The information  on Urban and Peri-urban Dairy production system was collected using structured interview schedule  from 120 households rearing cattle and buffalo from urban and peri-urban area. The results showed  that majority of the respondents were having high dairy farming experience and buffalo was the  preferred animal rather than cow. Majority of the farmers timely fed colostrum to newly born calves  (97.50%) but the practice of feeding mineral mixture to animals is still the matter of concern. Majority  of farmers were relying on natural service for breeding their bovines. Majority of farmers cleaned  shed at regular interval to avoid infection and majority of them vaccinate their animals against one or  the other diseases.
Keywords: Dairy production system; peri-urban; urban; semi-arid; Uttar Pradesh